Malam tanpa gelap - Dewi Yulianti; 2000; Elva Dina Elviana; Rizkia Fitri Ramadani; Ia Nuraini Rahmawati; Puji Lestari; 2001; Yesi Yulistiawati; Meta Sucianti; Risti Tantia; 2002; Virani Wulandari (Leutikaprio, 2017)
Buku ini berisi kumpulan cerita pendek